Evaluation of urinary antigen ELISA for diagnosing Legionella pneumophila serogroup 1 infection. Issue 8 (August 1990) - Birtles, R J; Harrison, T G; Samuel, D; Taylor, A G
Abstract : The enzyme linked immunosorbent assay (ELISA) described was developed to detect a soluble antigen in the urine of patients with Legionnaires' disease caused by Legionella pneumophila serogroup 1 (L.pn 1). The assay was evaluated and showed good specificity (100%) and intra-assay reproducibility. Antigen was detected in the urine of 93 (77%) of 120 patients, overall, and in 86% of patients from whom a specimen obtained within seven days of onset of illness was available. On all but one occasion the first urine sample taken from a patient for whom a positive ELISA result was obtained, was itself positive. In one case antigen was not detected at four days but was present on the fifth day after onset of symptoms. In two patients urinary antigen was detectable as early as two days after onset of symptoms. In another the antigen persisted for at least 60 days. More than half the patients, however, had stopped producing detectable antigen within 14 days of onset of symptoms. It is therefore important that where Legionnaires' disease is suspected urine is collected as early as possible in the course of the disease.